Strategy for Accelerating Poverty Reduction in Klungkung Regency, Bali - Sudipa, Nyoman; Nurjani, Putu Suda (Research and Development Agency Ministry of Home Affairs, 2021)
Poverty is an illustration to determine a householdâ€™s ability to fulfill fundamental rights or the necessities of a decent and dignified life as measured by the poverty line. Klungkung Regency, in the last five years, has made efforts to accelerate poverty reduction through the macro side. It maintains economic growth, reduces inflation, increases investment, creates jobs, and the micro side, namely increasing income and reducing the burden on public spending. Through pro-poor, pro-employment, and pro-regional growth programs. This research aimed to determine the poverty conditions and the reduction in the percentage of poor people in the Klungkung. The research method used quantitative and qualitative approaches, using government data sources and narrated qualitatively. This research uses the theory of poverty culture, various innovative development programs, and poverty to reduce the percentage and number of poor people from year to year. In 2016 the percentage of poverty was 6.35%, or the number of poor people was 11,210. In 2017 the percentage of poor people was 6, 29%, or the number of poor people by 11,150. In 2018 the percentage of poor people was 5.86%, or the number of poor people was 10,430. In 2019, the percentage of poor people was 5.4%, or the number of poor people was 9,960 people. In 2020 the percentage of poor people was 4.87%, or the number of poor people is 8,760. It is expected that by the end of 2023, the percentage of poverty in Klungkung Regency will be 3%, according to the target of the National Mediumâ€Term Plan (RPJMN).